Analisis Prosedur dan Syarat Pembiayaan Murabahah Dan Resiko Pembiayaan Murabahah Dan Resiko Pembiayaan Murabahah Pada Bank Muamalat Indonesia Cabang Tegal - Regina Maretha; Dewi Indriasih (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2022)
This research was conducted aiming to find out what are the requirements and how the procedures for Financing with Murabahah Contracts at Bank Muamalat Indonesia Tegal Branch and the Risks of Financing with Murabahah Contracts at Bank Muamalat Tegal Branches. The method used in this research is descriptive qualitative obtained through interviews with resource persons who handle Murabahah Financing at Bank Muamalat Tegal Branch. The results showed that the procedures and conditions in the distribution of funds in the form of Murabahah Financing at Bank Muamalat Indonesia Tegal Branch were not only carried out based on the provisions of Islamic Law/Shari'ah and the provisions of Islamic Banking Law, but also based on special provisions that existed at Bank Muamalat Indonesia Tegal Branch in the form of Standard Operating Procedures (SOP) of Bank Muamalat Indonesia Tegal Branch. And also the risks faced by Bank Muamalat Tegal Branch are caused by 3 factors, namely: 1. Internal Factors (Islamic Banks), 2 External Factors (Customers), and 3. Fictitious Factors.